PERLINDUNGAN HUKUM TERHADAP PEREMPUAN ADAT ATAS PENGELOLAAN SUMBER DAYA ALAM - Herlina Manik; Suhermi Suhermi; Sasmiar Sasmiar (Ensiklopedia of Journal, 2023)
Abstract: Indonesia upholds the principle of equality as regulated in the constitution. Recognizing the principle of equality means eliminating discrimination, because according to this principle the status of men and women is not different. However, due to Indonesia's strong patriarchal culture, there is still a lot of discriminatory and unfair treatment against women in its implementation. Until now, indigenous women still experience various types of rights violations. Indigenous women experience a lot of discrimination by their indigenous communities, companies and the state. The specific objectives to be achieved by researchers in this study are to examine and analyze the existence of indigenous women in managing natural resources and to examine and analyze regulations regarding government efforts to protect indigenous women. This research combines qualitative research through primary data collection in the field, conducting observations, as well as using secondary data especially related to government policies, regulations and programs to provide a general understanding of the real conditions faced by Indigenous Women compared to national policies. Based on this study, it is hoped that it will produce findings regarding the form of women's roles and participation to prove their existence in managing natural resources and also see the efforts of local governments and indigenous peoples to provide protection for women to manage natural resources.Keywords: Legal Protection, Indigenous Women, Natural Resources